"Physiological" Ear Clicking: Its Origin and Potential Usability as a Test Tool for the Eustachian Tube Function. Issue 4 (April 2016) - Ehrt, Karsten; Fischer, Hans-Georg; Dahl, Rüdiger; Punke, Christoph; Ovari, Attila; Pau, Hans Wilhelm
Abstract : Objective: To explore the origin of "physiological" ear clicks during deglutition or other pharyngeal movements, which, in contrast to disturbing frequent clicks under pathologic conditions, mostly remain unnoticed by the patient. Study Design: Clinical experimental study at a tertiary referral center. Methods: Ear clicks were recorded by a microphone sealing the external ear canal parallel to endoscopic or manometric evaluations of the Eustachian tube function. Results: Obviously, the acoustic signals (clicks) appear when the tube opens. The clicks might be explained by a disruption of fluid or mucus films covering the mucosa. As in our tests clicks could be recorded regularly, they might potentially be used as indicators in a new tube function test, which has to be elaborated. Abstract : Supplemental Digital Content is available in the text.